Genetic improvement of curry leaf in India: Challenges and future prospects - Raghu, B R; Aghora, T. S.; Dhananjaya, M. V. (Indian Horticulture, 2020)
Curry leaf is a multi-utility commercial crop with low investment cost and huge export value. Crop improvement in terms of research progress and area under cultivation is still in nascent stage for curry leaf in India. PGR management needs to be strengthened by more and more exploration programmes and establishment of field gene banks. Multi-environmental systematic evaluation of genetic resources with broad genetic base with increasing use of latest genomic resources for trait specific characterization and trait discovery for pharmaceutical and nutraceutical properties has to be given emphasis. To harness benefits out of present growing demands and new found horizons of applications, area under curry leaf needs to be expanded to small and marginal farmers. To achieve towards this end, farmers’ friendly technologies like high yielding varieties with inbuilt resistance to biotic and abiotic stresses are to be developed in addition to suitable protection techniques. By doing this, in near future, curry leaf will be proved to be very good alternative crop to small and marginal farmers for climate resilient agriculture.